Study on Genetic Coadaptability of Wild Quail Population in China - Guo-bin Chang; Hong Chang; Xiang-ping Liu; Wen-ming Zhao; Wei Xu; Hui-ying Wang; Wei Sun; Lei Tu; Sheng-xia Lu; Ming Xu; Qin-hua Huang; Olajide Olowofeso (The Journal of Poultry Science, 2004)
Genetic coadaptability in two neutral loci (Mpi-I and Es-D) was studied in wild quail population which settled down in Weishan Lake area in China, after that a new statistical model of genetic coadaptability was put forward and examined. Results showed that the model is suitable to test the genetic coadaptability, which exists in two loci, and genetic coadaptablity accounts for more than one third in the population genetic disequilibrium coefficient. Moreover, the population linkage disequilibrium was broken down by this effect. Therefore, genetic coadaptability is one of the key factors to the genetic disequilibrium in the population and reflects important information of evolutionary history. It can be applied to studying population phylogenetic differentiation, genetic structure evaluation and phylogenetic relationship. It is therefore very important and should attract much more attention on studying population genetic constitution.